Design and Experimental Evaluation of a Mid-Drive Electric Bicycle with BLDC Motor Bracket and Gearbox Integration - Agus Harijono; Rizki Priya Pratama; Nicky Suwandhy Widhi Supriyanto; Ahmad Hanif Firdaus; Nurhadi Nurhadi; Santoso Santoso (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
Electric bicycles with mid-drive systems provide better weight balance and performance, particularly on uphill terrain. However, their production cost is generally higher than hub-drive systems, limiting accessibility for wider users. This study aims to develop a cost-effective mid-drive conversion system by modifying a hub-drive e-bike using a custom steel bracket and an integrated gearbox, and to evaluate its power performance and energy efficiency. The prototype was powered by a 60V 15Ah LiFePO₄ battery and tested under laboratory and road conditions, including no-load, flat-road, and uphill tracks (5°–15° slopes). Data were collected using a tachometer, GPS, and PZEM-015 module to record speed, voltage, current, and power consumption. The motor required 659 W during acceleration from 0–10 km/h, decreased to 183 W at 19 km/h, and increased to 867 W at 39 km/h. Under a 15° incline, the e-bike maintained 15 km/h with 1120 W of power. Distance-based tests (2.08–4.07 km) showed stable energy consumption between 21–26 Wh/km, increasing proportionally with rider weight. The gearbox-assisted mid-drive conversion improved torque distribution, transmission efficiency, and energy performance, providing a practical and affordable alternative for developing efficient electric bicycles.